2022
DOI: 10.3390/polym14173562
|View full text |Cite
|
Sign up to set email alerts
|

The Reinforcing Effect of Waste Corrugated Paper Fiber on Polylactic Acid

Abstract: To improve the recycle value of waste paper and promote circular economic development, waste corrugated paper fiber (WCPF) was used as a reinforcing agent to prepare waste corrugated paper fiber/polylactic acid (WCPF/PLA) composites via dichloromethane solvent which can be reused. The WCPF in the waste corrugated paper is extracted by beating in a Valli beating machine for different time lengths and grinding in a disc grinder. The effects of beating time and the content of WCPF on the microstructure, mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…As expected, WP addition (5–30 wt.%) increased the mechanical properties of the composite compared to neat PLA, such as their tensile (5–22%) and flexural (5–50%) strengths, while decreasing thermal stability (3–24%). The composite with 25 wt.% and 30 min of beating time provided the optimum mechanical performance, for which the authors concluded that this material could solve the environmental issues related to paper recycling [ 82 ].…”
Section: Waste Paper-polymeric Compositesmentioning
confidence: 99%
“…As expected, WP addition (5–30 wt.%) increased the mechanical properties of the composite compared to neat PLA, such as their tensile (5–22%) and flexural (5–50%) strengths, while decreasing thermal stability (3–24%). The composite with 25 wt.% and 30 min of beating time provided the optimum mechanical performance, for which the authors concluded that this material could solve the environmental issues related to paper recycling [ 82 ].…”
Section: Waste Paper-polymeric Compositesmentioning
confidence: 99%
“…To improve the properties, several efforts have been made to fill PLA with different natural fillers as a disperse phase to modify the polymer chain mobility and consequently enhance its properties [ 3 , 4 , 5 , 6 ]. Most of the PLA have low crystallinity (3–10%), and filler addition was reported to significantly improve PLA crystallinity by reorganizing the polymeric chains and influencing the crystallization rate via heterogeneous nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…It is a promising way to use waste paper for the preparation of composite materials. Su et al [34] found that waste corrugated paper fibers (WFs) can obviously improve the tensile strength, flexural strength, and deformation resistance of WF/PLA composites, and WFs can be uniformly dispersed in the PLA matrix by a solvent.…”
Section: Introductionmentioning
confidence: 99%